Pendidikan Islam sebagai Solusi Alternatif untuk Mengatasi Kemerosotan Moralitas Anak Bangsa - Bahroni Bahroni (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
: Multidimensional crisis at our country is based on value (akhlak) crisis that emerge from lack of spiritual intelligence. To solve this complex problem, we need spiritual quotient development that based on lofty values namely iman, Islam, and ikhsan principle, so that we can optimize emotional quotient and intellectual quotient all at once.Â Â